(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This paper examines the key challenges and prospects for Uzbekistan’s transition to a green economy. Particular attention is paid to environmental and socio-economic issues associated with the consequences of the Aral Sea disaster, the water crisis, and atmospheric pollution. The analysis identifies structural, institutional, and financial barriers hindering the effective implementation of green technologies. The article explores policy directions including the national strategy for low-carbon development, reforms in the energy and water sectors, and renewable energy initiatives. It concludes that a comprehensive approach integrating the efforts of government, business, and civil society is essential for achieving sustainable economic growth and environmental security.